The Binding Mode and Molecular Dynamics of Epigallocatechin and Epigallocatechin Gallate with Human Superoxide Dismutase 1 in Complex with a Naphthalene-Catechol Linked Compound - Levita, Jutti; Bawono, Lidya Cahyo; Khairinisa, Miski Aghnia; Jiranusornkul, Supat; Megantara, Sandra; Ikhsan, Muhammad (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Superoxide dismutases (SODs) are metalloenzymes that defend the body against reactive oxygen species and contribute to combating inflammation. Human cells have three distinct SODs, i.e., manganese SOD (MnSOD), extracellular SOD(ECSOD), and copper-zinc SOD (Cu-ZnSOD) or SOD1. The crystal structure of human SOD1 in a complex with a naphthalene-catechol-linked compound revealed hydrogen bonds and hydrophobic interaction. Catechins arepolyhydroxylated polyphenols contained in the leaves of Camellia sinensis L. This work aims to study the binding mode and molecular dynamics of two major catechins, epigallocatechin (EGC) and epigallocatechin gallate (EGCG) with human SOD1 (in complex with SBL1, a naphthalene-catechol linked compound). Both catechins demonstrated a binding mode with the enzyme, in terms of hydrogen bonds and hydrophobic interaction, similar to the native ligand (SBL1). Of the two catechins, EGC possesses a better binding affinity (docking score of -4.15 kcal/mol) for human SOD1 compared to EGCG (docking score of -4.02 kcal/mol), thus the EGC-SOD1 complex was continued in MD simulation to investigate the conformational stability and time-dependent ligand binding ability in the binding pocket. The molecular dynamics simulation confirmed that EGC is more stable than the native ligand, SBL1, with the RMSD average value of SBL1 and EGC being 1.1669 Å and 0.5607 Å, respectively. Taken together, this study confirms the antioxidant activity of catechins in C. sinensis L.